Case Report: Trilostane therapy in a dog with recurrent adrenocortical carcinoma producing an array of steroid hormones - Cheung, Chloe; Giori, Luca; Griebsch, Christine; Courtman, Natalie; Podadera, Juan; Thompson, Mary (Frontiers in Veterinary Science, 2025)
Case summaryA 10-year-old neutered male poodle-cross was presented with signs of progressive hyporexia and marked polyuria and polydipsia (PU/PD) of 2 months' duration. Right unilateral adrenalectomy was performed 24 months prior, and adrenocortical carcinoma with no evidence of metastatic disease was diagnosed. Tumor aldosterone secretion was suspected due to persistent hypokalaemia and systemic hypertension. Upon re-presentation, the dog had a pot-bellied appearance, dermatological changes (symmetrical alopecia along the trunk, elbows, and hocks, with decubital ulcers), systemic hypertension, and marked hypokalaemia unresponsive to oral potassium supplementation, raising concerns for an endocrine disorder. Abdominal CT confirmed mass lesions in multiple liver lobes near the previous adrenalectomy site, and cytology confirmed adrenocortical carcinoma metastases. Regional and cranial mediastinal lymphadenomegaly, as well as prostatomegaly, were observed, while no abnormalities were detected in the left adrenal gland. A serum adrenal profile identified marked elevations in progesterone, androstenedione, estradiol, and testosterone concentrations pre- and post-ACTH. Serum aldosterone and cortisol concentrations pre- and post-ACTH were within reference intervals, noting the dog had been treated with spironolactone for 8 weeks at measurement. Trilostane therapy was initiated with an initial positive response, including reduced PU/PD and resolution of pot-bellied appearance. A significant reduction of steroid hormones was documented later. Signs returned about 4 months into trilostane treatment with evidence of progressive disease on repeat CT and adrenal profile. The dog is managed with palliative trilostane, 14 months since liver metastasis diagnosis.Relevance and novel informationThis case highlights an initial clinical response to trilostane in a dog with metastatic, functional adrenocortical carcinoma (ACC), demonstrating short-term control of clinical signs. The variation in presentation between initial diagnosis and relapse prompted a hypothesis of a shift in tumor steroidogenic activity—a phenomenon rarely documented in veterinary literature. It underscores the diverse manifestations arising from excess production of multiple steroid hormones, including precursors. It also supports adrenal profiling in complex cases and confirms trilostane's utility as a palliative therapy in non-resectable or metastatic ACC.